Pengaruh Komunikasi, Motivasi dan Lingkungan Kerja terhadap Semangat Kerja PT Andarta Muzizat Balikpapan - Rizky; Misna Ariani; Imam Arywibowo; Didik Hadiyatno; Pudjiati Pudjiati; Tutik Yuliani (Fakultas Ekonomi Universitas Balikpapan, 2022)
The purpose of this study was to determine the effect of Communication, Motivation and Work Environment on the Spirit of Work Employees at PT Andiarta Muzizat Balikpapan. This type of research uses quantitative research. The sample in this study were 82 employees of PT. Andiarta Muzizat Balikpapan uses saturated sampling technique. The method used are instrument test, classic assumption test, multiple regression analysis and hypothesis testing. The results of the analysis show that Communication (X1) has a significant effect on Spirit of Work (Y). Motivation (X2) has a significant effect on Spirit of Work (Y). Work Environment (X3) has a significant effect on Spirit of Work (Y).